Spinal lipoma as a dysembryogenetic anomaly: Four unusual cases of ectopic iliac rib within the spinal lipoma. Issue 7 (18th April 2016) - Accogli, Andrea; Pavanello, Marco; Accorsi, Patrizia; De Marco, Patrizia; Merello, Elisa; Pacetti, Mattia; Nozza, Paolo; Fiorillo, Chiara; Pinelli, Lorenzo; Cama, Armando; Rossi, Andrea; Catala, Martin; et al.
Abstract : Background: Congenital spinal lipomas are closed spinal dysraphisms belonging to the neural tube defects (NTDs) group. They include a broad spectrum of lesions ranging from simple lipomas of the filum terminale to complex malformations. On histological evaluation, various tissue components of ectodermal, mesodermal or endodermal origin are found within the lipomas, with prevalence for nerves and striated muscle and, more rarely, cartilage and bone. Overall, rib malformations have been occasionally observed in patients with NTDs and in NTD mouse models. However, an ectopic rib arising within the spinal lipoma and articulating with the iliac crest has not been reported in either animal models or in humans. Cases: We describe four patients affected by lipomyeloschisis or lipomyelomeningocele, with an unusual fibrocartilaginous protuberance arising within the lipoma and connecting to one iliac crest, strongly resembling an ectopic rib. Histological evaluation confirmed the presence of cartilaginous tissue. Conclusion: We expand the clinical spectrum of fibrocartilaginous anomalies associated with spinal lipoma, suggesting the presence of an ectopic rib as a new possible phenotype in NTDs. A careful analysis by neuroradiologists and pathologists should be performed in spinal lipomas to assess the presence of an ectopic rib or other uncommon developmental anomalies. Furthermore, molecular studies are required to detect the genetic cause of this unusual phenotype. Birth Defects Research (Part A) 106:530–535, 2016. © 2016 Wiley Periodicals, Inc.